Huoxue Huatan Decoction Ameliorates Myocardial Ischemia/Reperfusion Injury in Hyperlipidemic Rats via PGC-1α–PPARα and PGC-1α–NRF1–mtTFA Pathways - Lin, Fei; Tan, Yu-Qing; He, Xuan-Hui; Guo, Li-Li; Wei, Ben-Jun; Li, Jun-Ping; Chen, Zhong; Chen, Heng-Wen; Wang, Jie (Frontiers in Pharmacology, 2020)
The aim of this study was to elucidate the preventive and therapeutic effects and the underlying mechanisms of Huoxue Huatan Decoction (HXHT) on myocardial ischemia/reperfusion (I/R) injury in hyperlipidemic rats. An I/R model was established in hyperlipidemic Wistar rats. After 4–8 weeks of HXHT treatment, the effects of HXHT on the physical signs of rats were observed. Lipid metabolism, myocardial enzyme spectrum, cardiac function, myocardial histomorphology, and mitochondrial biosynthesis were investigated by a biochemical method, ultrasonography, electron microscopy, pathological examination, real-time PCR, and Western blot. HXHT can affect the lipid metabolism at different time points, and significantly reduce the levels of cholesterol (CHO), triglyceride (TG), high-density lipid-cholesterol (HDL-C), and low-density lipid-cholesterol (LDL-C) in hyperlipidemic rats (P < 0.05 or P < 0.01); it can significantly reduce the levels of creatine kinase-MB (CK-MB) and lactate dehydrogenase (LDH), reduce the myocardial infarct size and myocardial ischemic area, and improve cardiac function. The results of myocardial histomorphology showed that HXHT could protect myocardial cells, relieve swelling, reduce the number of cardiac lipid droplets, and improve myocardial mitochondrial function. HXHT could significantly increase the levels of total superoxide dismutase (T-SOD) and succinate dehydrogenase (SDH) (P < 0.05 or P < 0.01), increase CuZn-superoxide dismutase (CuZn-SOD) and glutathione-peroxidase (GSH-Px) levels, and decrease the levels of malondialdehyde (MDA) (P < 0.05); it could increase the mRNA and protein expression levels of peroxisome proliferator-activated receptor-gamma coactivator 1 alpha (PGC-1α), peroxisome proliferator-activated receptor alpha (PPARα), nuclear respiratory factor 1 (NRF1), and mitochondrial transcription factor A (mtTFA) (P < 0.05 or P < 0.01), and increase the synthesis of mitochondrial DNA (mtDNA) (P < 0.01). HXHT can reduce myocardial I/R injury in hyperlipidemic rats. The protective mechanisms may involve a reduction in blood lipids, enhancement of PGC-1α–PPARα pathway activity, and, subsequently, an increase in fatty acid β-oxidation, which may provide the required input for mitochondrial energy metabolism. HXHT can additionally enhance PGC-1α–NRF1–mtTFA pathway activity and, subsequently, reduce antioxidative stress, promote mitochondrial mtDNA synthesis, and reduce mitochondrial damage. The two pathways use PGC-1α as the intersection point to protect mitochondrial structure and function, reduce I/R-induced injury, and improve cardiac function.